Marketing via friends: strategic diffusion of information in social networks with homophily - Roman Chuhay (Fondazione Eni Enrico Mattei (FEEM), 2010)
The paper studies the impact of homophily on the optimal strategies of a monopolist, whose marketing campaign of new product relies on a word of mouth communication. Homophily is a tendency of people to interact more with those who are similar to them. In the model there are two types of consumers embedded into a social network, which differ in friendship preferences and desirable design of product. Consumers can learn about the product directly from an advertisement or from their neighbors. The monopolist chooses the product design and price to influence a pattern of communication among consumers. We find a number of results: (i) for low levels of homophily the product attractive to both types of consumers is preferred to specialized products; (ii) the price elasticity is increasing in homophily; (iii) an increase in the homophily benefits both the monopolist and consumers; and (iv) the product attractive to both types may be optimal even if the monopolist obtains profits only from sales to one type of consumers.
Keywords: D21; D42; D60; D83; L11; L12; 330; Networks; Word of mouth; Viral marketing; Homophily; Diffusion; Social networks; Random graphs; Monopoly; Pricing strategy; Product design; Marketing; Advertisement